Linear Motion Coverage as a Determinant of Transparent Liquid Perception - Takahiro Kawabe (i-Perception, 2018)
When a transparent liquid flows, the background image behind the flow dynamically deforms due to light refraction. The dynamic deformations of a background image (dynamic image deformations) are one of the visual features used by the visual system to infer the existence of a transparent liquid flow. Although previous studies have discussed the role of the narrow band components of the spatiotemporal deformation frequency, it was still unclear whether motion signals, one of the constituents of dynamic image deformations, were the determinant of the perception of a transparent liquid. Manipulating the flow speed of image deformation, which is a critical parameter for changing motion signals in dynamic image deformations, we asked observers to judge whether a transparent liquid was included in the clips or not. We found that the proportions of reporting that they saw a transparent liquid increased with the flow speed of image deformations. Analyzing motion signals of the stimulus clips, we found that the faster the flow of image deformations the fewer linear motion signals were contained. The results indicate that the perception of a transparent liquid arises when the dynamic image deformations contain fewer linear motion signals.